Mesoporous solid acid catalysts esterifying waste cooking oil to biodiesel at room temperature. (19th March 2023) - Krishnaveni, M.; Kannan, Chellapandian
Abstract: This work presented the preparation and characterization of mesoporous AlPO4 and AlSiO4 by the sol-gel method with the help of isopropylamine as a template. Isopropylamine is a microporous template and it creates only 0–2 nm pores but in the present study, the same template creates mesoporosity in AlPO4 and AlSiO4 . The synthesized material properties are characterized by XRD, IR, TGA, BET, TPD, SEM-EDX and HR-TEM. The results confirmed that the synthesized materials are crystalline, tetrahedral framework, thermal stability (800 °C), mesoporosity of AlPO4 (9 nm) and AlSiO4 (7 nm), the acidity of AlPO4 is 0.53 mmol/g and AlSiO4 is 1.16 mmol/g and it exhibits crystalline morphology. Catalytic activities are verified by biodiesel synthesis from waste cooking oil (WCO) as a low-cost feedstock by transesterification reaction. It was identified that the maximum selectivity of biodiesel over AlPO4 and AlSiO4 (89 and 96%) was achieved at room temperature. These catalysts are active at room temperature may be due to their porous nature. The results revealed that AlSiO4 is a more effective catalyst to synthesize biodiesel than AlPO4 . These catalysts are environmentally friendly and reusable with the same efficiency. Graphical Abstract: UF0001